Prevalence, Cause, and Associated Factors of Visual Impairment Among Diabetic Patients at the Debre Tabor General Hospital, Northwest Ethiopia. (September 2022) - Mersha, Getasew Alemu; Alimaw, Yezinash Addis; Belete, Gizachew Tilahun; Woredekal, AsamereTsegaw
Introduction: Visual impairment is a major public health challenge for diabetics who have ocular comorbidities. In Ethiopia, data are lacking on the prevalence of visual impairment among diabetics as well as information on causes and predisposing factors. The current study was designed to assess the causes, risk factors, and levels of diabetes-related visual impairment within an Ethiopian population.Methods: The study enrolled a total of 296 diabetic patients at the Debre Tabor General Hospital (DTGH). Data were ascertained through face-to-face interview, from patients' medical folder, and through comprehensive ocular health assessment. Descriptive and analytical statistics were performed.Result: Generally, the prevalence of visual impairment among adult diabetic patients was 39.5% (95% confidence interval [CI]: 33.8–45.6). Visual impairment was primarily due to diabetic retinopathy (44.4%), followed by refractive error (20.6%), cataract (13.9%), other ocular conditions (6.1%), and glaucoma (5.4%). Age >45 years (adjusted odds ratio [AOR] = 7.8, 95% CI: 3.5–18), female gender (AOR = 3.0, 95% CI: 1.4–7.7), low educational status (AOR = 8.1, 95% CI: 2.4–26.0), and longer span of diabetes (AOR = 3.7, 95% CI: 2.1–6.8) had a notable association with visual impairment among diabetic patients.Discussion: This study observed a high prevalence of visual impairment in diabetic patients. Diabetic retinopathy, refractive error, and cataract were the most common causes of visual impairment, followed by other ocular conditions and glaucoma. Older age, female gender, low educational status, and longer span of diabetes were important risk factors of visual impairment among diabetic patients.Implications for Practitioners: This result could alert health care professionals to inform their diabetic clients about the serious impacts of diabetes and the need for a regular eye check-up. Health care providers and policy makers should work to integrate the diabetic clinics into a general hospital with an eye care unit for an effective screening of diabetic eye disease and prevention of blindness.